Improving Students Procedural Writing Skills through Project Learning with Canva Utilization - Ayu Warastuti; D.B. Putut Setiyadi; Purwo Haryono; Hersulastuti (Journal of Educational Management Research, 2025)
This study investigates the impact of integrating Project-Based Learning (PjBL) supported by Canva on procedural writing skills among eighth-grade students at SMPIT Muhammadiyah An Najah Jatinom. The research aimed to enhance student engagement, motivation, and writing performance by using digital tools in a bilingual Islamic education context. The results showed significant improvements in students' writing, with the percentage of students meeting the minimum mastery criterion increasing from 28% in the pre-test to 82% in Cycle II. The study employed Classroom Action Research (CAR) with iterative cycles of planning, action, observation, and reflection. Data were collected through qualitative methods (observations, interviews, field notes) and quantitative methods (writing tests). The findings confirm that PjBL and Canva effectively support multimodal literacy, foster collaboration, and enhance writing skills. The study contributes to educational practice by offering a model for integrating digital tools into PjBL, particularly in bilingual classrooms. Future research should explore the long-term effects and the application of this approach to other genres of writing and educational settings.